Implementasi Kegiatan Ekstrakurikuler Pramuka Dalam Meningkatkan Kepercayaan Diri Siswa di MTs Al-Muta’allimin Patokbeusi Subang - Hanifah, Nur; Solihatudiniyah, Lela Salamah; Nuralim, Iman; Mondari, Mondari; Azkiya, Khoirul; Tarsono, Tarsono (CV. Rayyan Dwi Bharata, 2024)
Self-confidence is one of the important aspects of one's life. High self-confidence can motivate someone to achieve and succeed. Scout extracurricular activities can be one of the means to improve students' self-confidence This study aims to determine the implementation of scout extracurricular activities in improving the self-confidence of students of Madrasah Tsanawiyah Al-Mutaallimin Patokbeusi Subang. The method used in this research is a qualitative approach with descriptive research type. The techniques used are interviews, observation and documentation. Based on the research results, it is known that the implementation of scout extracurricular activities in increasing the self-confidence of students who are members of the scout movement at Madrasah Tsanawiyah Al-Mutaallimin Patokbeusi Subang for the 2023/2024 academic year has gone as expected. This can be proven by achieving indicators of self-confidence, namely students are more courageous in expressing their opinions in public, students are more courageous to try new things and students are more confident in facing challenges. Through the process of increasing students' self-confidence which can grow through routine training, through the opening and closing ceremonies of scouting, and by implementing or practicing the Basic Principles of Scouting and the Scout Code of Honor (Trisatya and Dasa Darma pramuka).